2017
DOI: 10.1289/ehp500
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Urinary Triclosan Concentration in Relation to Maternal and Neonatal Thyroid Hormone Levels: A Prospective Study

Abstract: Background:Triclosan (TCS) is a synthetic antibacterial chemical widely used in personal care products. TCS exposure has been associated with decreased thyroid hormone levels in animals, but human studies are scarce and controversial.Objective:We evaluated the association between maternal TCS exposure and thyroid hormone levels of mothers and newborns.Methods:TCS was measured by high-performance liquid chromatography–tandem mass spectrometry (HPLC-MS/MS) in urine samples collected during gestational weeks 38.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 34 publications
(43 reference statements)
6
69
3
Order By: Relevance
“…were immediately frozen and stored at −80°C for measurement of thyroid hormones. These exposure doses of TCS were set based on the exposure levels of human and wildlife [9,14] . 3-100 ng/mL was close to the levels of urinary TCS concentrations in Chinese pregnant women [9] as well as TCS levels in some rivers/lakes [3] .…”
Section: Tcs Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…were immediately frozen and stored at −80°C for measurement of thyroid hormones. These exposure doses of TCS were set based on the exposure levels of human and wildlife [9,14] . 3-100 ng/mL was close to the levels of urinary TCS concentrations in Chinese pregnant women [9] as well as TCS levels in some rivers/lakes [3] .…”
Section: Tcs Exposurementioning
confidence: 99%
“…These exposure doses of TCS were set based on the exposure levels of human and wildlife [9,14] . 3-100 ng/mL was close to the levels of urinary TCS concentrations in Chinese pregnant women [9] as well as TCS levels in some rivers/lakes [3] . We used DMSO as a solvent to enhance its solubility because TCS has low water solubility [15] , and the concentration of DMSO in both the experimental and control groups was 0.01%.…”
Section: Tcs Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…It is currently classified as a contaminant of emerging concerns, mainly due to its demonstrated absorption as it has been detected in breast milk, blood and urine. The substance has been associated to increased fetal testosterone levels in humans [70] and higher weight at birth. A link with gestational diabetes mellitus has been indicated but is as yet unconfirmed.…”
Section: Other Preservatives/antimicrobialsmentioning
confidence: 99%
“…However, numerous recent epidemiological studies report detrimental TCS effects on human health, including problems with thyroid function (Wang et al, 2017), reproduction (Hua et al, 2017), and immune function and development (Wei et al, 2017;reviewed in Weatherly & Gosse, 2017). Additional recent epidemiological studies have revealed increased risks due to TCS exposure of gestational diabetes (Ouyang et al, 2018), abnormalities of sperm morphology (Jurewicz et al, 2018) and lowered cognitive test scores in children (Jackson-Browne et al, 2018).…”
Section: Introductionmentioning
confidence: 99%